2007
DOI: 10.1111/j.1365-2702.2006.01891.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life concerns and end‐of‐life care preferences of aged persons in long‐term care facilities

Abstract: The results reveal the major QOL concerns among the older residents living in long-term care facilities. This study, which is an initial step in profiling the older people's end-of-life care preferences, also shed light on how to formulate advance care planning in long-term care facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 35 publications
(36 reference statements)
3
87
0
1
Order By: Relevance
“…The Chinese Version of the Cumulative Illness Rating Scale (CIRS) 6 was used to capture comorbid conditions, which were confirmed by the medical record. Physical functional status was collected using the Chinese version of Personal Activity of Daily Living (P-ADL) and Instrumental Activity of Daily Living (I-ADL); the score of P-ADL or I-ADL was the sum value of all 8 items in each scale which range from 8 to 24.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Chinese Version of the Cumulative Illness Rating Scale (CIRS) 6 was used to capture comorbid conditions, which were confirmed by the medical record. Physical functional status was collected using the Chinese version of Personal Activity of Daily Living (P-ADL) and Instrumental Activity of Daily Living (I-ADL); the score of P-ADL or I-ADL was the sum value of all 8 items in each scale which range from 8 to 24.…”
Section: Data Collectionmentioning
confidence: 99%
“…7 Another Hong Kong study identified that many nursing home residents were uncertain or uncomfortable when asked about stating their preferences for life-sustaining treatment, with many leaving this question unanswered. 6 In traditional Chinese culture, death is a very sensitive issue, and a topic to be avoided, with those who do mention death considered sacrilegious. 8 Most older Chinese people consult their relatives, especially their oldest son, before making health care decisions.…”
mentioning
confidence: 99%
“…A survey of Chinese residents found that most respondents were neutral, rather than negative, toward passive euthanasia (Ming- Lin Chong & Shiu-Yeu, 2009); and in contrast to the traditional Chinese preference for elders of a family to make decisions for the patient, the patient was thought of as the main decision maker in decisions about euthanasia (Ming- Lin Chong & Shiu-Yeu, 2009). In a survey of residents of Hong Kong long-term care facilities, Chan and Pang (2007) found that respondents were willing to discuss death and dying, although they had not made end-of-life care plans, and wanted to defer to their physicians to make these decisions for them. Finally, a 2007 survey of Hong Kong residents found that only a minority adhered to traditional views about death and dying, but still only 10% were interested in receiving information about hospice (Mjelde-Mossey .…”
Section: Hospice Care In Hong Kongmentioning
confidence: 97%
“…16,17 To the authors' knowledge, none has been done with focus also on health care assistants (HCA), comparing them with the professional staff in old age homes. Therefore, the objective of this study would be to explore and compare in depth the needs, knowledge and readiness, and key concerns of old age home staff before providing palliative care.…”
Section: Introductionmentioning
confidence: 98%